Simultaneous control for the heat equation with Dirichlet and Neumann boundary conditions - Burq, Nicolas; Moyano, Ivan (Comptes Rendus. Mathématique)
It is well known that both the heat equation with Dirichlet or Neumann boundary conditions are null controlable as soon as the control acts in a non trivial domain (i.e. a set of positive measure). In this article, we show that for any couple of initial data $(u_0, v_0)$ we can achieve the null control for both equations (Dirichlet and Neumann boundary conditions respectively) simultaneously with the same control function for both equations.